Polyester and / or copolyester, preparation method thereof and catalyst used therein

By adding borate ester and alkali metal compounds to the catalyst, the hydroxy acid modified titanate catalyst is improved, and the problems of insufficient polymerization activity and poor polyester quality are solved, thereby achieving high activity and high quality polyester preparation.

CN116444777BActive Publication Date: 2025-03-21喀什地区第一人民医院
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310497489.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-05
Publication Date
2025-03-21
Estimated Expiration
2043-05-05

AI Technical Summary

Technical Problem

The existing hydrolysis-resistant titanium-based catalysts used for the preparation of polybutylene terephthalate (PBT) and its copolyester have insufficient polymerization activity, resulting in poor polyester quality.

Method used

Using a catalyst containing a titanium compound and a borate compound, the molar ratio of the borate to the titanium compound is 0.01-0.5:1, the titanium esters are modified by hydroxy acid modification, and alkali metal compounds and/or ammonium compounds are added to improve the activity of the catalyst.

Benefits of technology

The activity of the catalyst is significantly improved, the quality of the polyester is improved, including the increase in intrinsic viscosity and slice hue, and the acid value and by-product tetrahydrofuran content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004212712320000061
    Figure BDA0004212712320000061
Patent Text Reader

Abstract

The present invention discloses a polyester and / or copolyester, a preparation method thereof and a catalyst used therein. The polyester and / or copolyester has high intrinsic viscosity and good chip quality, and the preparation method thereof comprises: (1) mixing a Ti(OR)4 general formula compound, a hydroxy acid compound, a boric acid ester, an alkali metal compound and / or an ammonium compound and an optional solvent to obtain a catalyst through reaction; (2) using the obtained catalyst for the synthesis of the polyester and / or copolyester.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses polyester and / or copolyester, a preparation method and a catalyst used therefor, and belongs to the technical field of polymer synthesis. Background Art

[0002] Polybutylene terephthalate (PBT) and its copolyesters such as polybutylene terephthalate-adipate (PBAT), polybutylene terephthalate-succinate (PBST), etc., are thermoplastic polyester materials formed by esterification and polycondensation of aliphatic dibasic acid and / or aromatic dibasic acid and butanediol (BDO) under the action of a catalyst. PBT and its copolyesters have good mechanical and thermal properties and have important applications in many fields. For example, PBT can be used as engineering plastics in automobiles, machinery, instruments, electronics and electrical, etc., and PBAT can be used as a biodegradable plastic to reduce ground film, disposable shopping bags, etc.

[0003] At present, the commonly used catalysts for the synthesis of PBT and its copolyesters are organic titanate compounds such as tetrabutyl titanate, tetraisopropyl titanate, etc. However, titanate compounds are easy to react with water in the reaction system and decompose to produce solid oxides, which reduces the catalytic efficiency on the one hand; on the other hand, the long-term deposition of solid oxides will cause filter blockage, hinder heat transfer, lead to shutdown and cleaning, and thus cause economic losses. Therefore, it is necessary to treat the catalyst for hydrolysis resistance. Patent [CN1720216A] discloses a catalyst composition obtained by the reaction of titanium alkoxide, hydroxy acid and base, which can be used for the preparation of PBT, and the catalyst has good hydrolysis resistance. Patent [CN10684189A] discloses a liquid titanium catalyst, which is prepared by the reaction of tetrabutyl titanate, 1,4-butanediol, phosphate, hydroxy acid, ethyl orthosilicate and metal acetate. When used in the preparation of aliphatic copolyesters, it has the characteristics of high activity, good slice color and catalyst hydrolysis resistance.

[0004] However, the inventors have found through a large number of experimental studies that the hydrolysis-resistant titanium catalyst modified with hydroxy acid has insufficient polymerization activity and poor polyester quality when used in the preparation of butylene terephthalate (PBT) and its copolyesters. This is because the chelation of hydroxy acid reduces the coordination ability of titanium and ester carbonyl during the polymerization process, resulting in insufficient activity. The reduced catalytic activity and long-term high temperature conditions lead to reduced polyester quality. Therefore, it is urgent to develop a hydrolysis-resistant catalyst with better catalytic performance and use it to prepare polyesters and copolyesters with better performance. Summary of the invention

[0005] One of the purposes of the present invention is to provide a hydrolysis-resistant catalyst with good catalytic performance, which has the characteristics of high polymerization activity and good chip color when used for the polymerization of polybutylene terephthalate (PBT) and its copolyester.

[0006] A second object of the present invention is to provide a method for preparing a catalyst corresponding to the first object.

[0007] The third object of the present invention is to provide a method for preparing polyester and / or copolyester, which uses the catalyst of the first object or the catalyst obtained in the second object.

[0008] The fourth object of the present invention is to provide polyester and / or copolyester obtained by the preparation method described in the third object.

[0009] To achieve the above object, the technical solution adopted by the present invention is: a catalyst for polyester and / or copolyester, the catalyst contains a titanium compound and a borate compound, wherein the molar ratio of the borate to the titanium compound (calculated as boron element and titanium element) is 0.01-0.5:1.

[0010] In the above technical solution, the titanium compound is a reaction product of a compound having the general formula Ti(OR)4 and a hydroxy acid, R is a straight chain or branched alkyl group selected from 1 to 10 carbon atoms, preferably one of tetramethyl titanate, tetraethyl titanate, tetraisopropyl titanate and tetrabutyl titanate. The hydroxy acid is an organic acid containing one or more hydroxyl groups, preferably an organic acid containing 1 to 3 hydroxyl groups, more preferably at least one selected from citric acid, lactic acid, malic acid, tartaric acid, 2-hydroxyglutaric acid, 2-hydroxybutyric acid, glycolic acid, mandelic acid and salicylic acid;

[0011] Preferably, the molar ratio of the Ti(OR)4 compound to the hydroxy acid is 1:(1-4).

[0012] In the above technical solution, the borate ester is at least one of trimethyl borate, triethyl borate, triisopropyl borate, tributyl borate, triethylene glycol borate, tripropylene glycol borate and tributyl glycol borate.

[0013] The addition of borate ester can significantly improve the activity of the catalyst. The reason may be that boron can promote the dissociation of the hydroxy acid group on hydroxy acid titanium and release the activity of the titanium catalyst.

[0014] In the above technical solution, the catalyst further contains an alkali metal compound and / or an ammonium compound;

[0015] Preferably, the alkali metal compound and / or ammonium compound is selected from at least one of hydroxide, oxalate, carbonate, bicarbonate, and carboxylate; and / or the metal in the alkali metal compound is selected from at least one of lithium, sodium, and potassium;

[0016] More preferably, the molar ratio of the alkali metal compound and / or ammonium compound to the hydroxy acid is (0.05-0.5):1.

[0017] The alkali metal compound and / or ammonium compound is mainly used to neutralize the acidity of the hydroxy acid and improve the problem of increased tetrahydrofuran by-products caused by the acidity of the catalyst.

[0018] In the above technical solution, the catalyst further includes a solvent; preferably: the solvent is water and / or an alcohol solvent, wherein the alcohol solvent is preferably one or more selected from C2-C10 monohydric alcohols and C2-C10 polyhydric alcohols;

[0019] To achieve the second objective, the technical solution adopted by the present invention is: a method for preparing a catalyst for polyester and / or copolyester, comprising: mixing (1) the Ti(OR)4 compound of general formula, (2) the hydroxy acid compound, (3) the boric acid ester, (4) the alkali metal compound and / or ammonium compound and (5) the optional solvent, and obtaining the catalyst through reaction.

[0020] In the above technical solution, the molar ratio of the borate ester to the titanium compound (in terms of boron element and titanium element) is 0.01-0.5:1. The molar ratio of the Ti(OR)4 compound to the hydroxy acid is 1:(1-4). The molar ratio of the alkali metal compound and / or ammonium compound to the hydroxy acid is (0.05-0.5):1.

[0021] In the above technical solution, the preparation method comprises:

[0022] (1) mixing the hydroxy acid compound and the optional solvent, and then adding the compound of the general formula Ti(OR)4 to obtain a mixed solution;

[0023] (2) The mixed solution is subjected to a temperature-raising treatment, and then a boric acid ester and an alkali metal compound and / or an ammonium compound are added to obtain the catalyst solution.

[0024] In the above technical solution, in the step (2), the temperature is raised to 50-200°C, preferably 50-150°C; and the treatment is performed for 0.2-24h, preferably 1-10h.

[0025] The method for preparing polyester and / or copolyester of the present invention comprises: (1) obtaining the catalyst of one of the above purposes or obtaining the catalyst by the preparation method of the second purpose; (2) using the catalyst in step (1) for polyester synthesis. Those skilled in the art can apply it according to existing process conditions, for example but not limited to using the catalyst composition for preparing polyester by polycondensation of polyacid and polyol, such as polyethylene terephthalate, polybutylene terephthalate, polypropylene terephthalate and polybutylene terephthalate-adipate.

[0026] The present invention further protects the polyester and / or copolyester prepared by the above preparation method.

[0027] In the present invention, the intrinsic viscosity, hue, etc. of the polyester and / or copolyester are tested by the following method:

[0028] (1) Intrinsic viscosity: Phenol-tetrachloroethane mixture was used as solvent and measured with an Ubbelohde viscometer at 25°C.

[0029] (2) Hue: The Hunter L value (brightness), a value (red-green hue) and b value (yellow-blue hue) were measured using an Agera colorimeter from Hunter Lab.

[0030] (3) Acid value: According to the provisions of method A in GB / T14190-2008. The mixed solvent is phenol-chloroform, with a volume ratio of 2:3. The standard titration solution is potassium hydroxide-benzyl alcohol, with a concentration of 0.01 mol / L, prepared and calibrated according to 4.24 of GB / T601-2002. The concentration of bromophenol blue indicator is 0.2%. Sample preparation: 0.5 g sample is dissolved in 25.00 mL of phenol-chloroform mixed solvent.

[0031] (4) By-product tetrahydrofuran (THF) content: determined by gas chromatography.

[0032] The present invention will be further described below by way of examples. DETAILED DESCRIPTION

[0033] [Example 1]

[0034] Add 262.5 g (1.25 mol) of citric acid monohydrate and 262.5 g of water to a three-necked flask equipped with an agitator, a condenser and a thermometer, and stir to dissolve. Use a dropping funnel to slowly add 170 g (0.5 mol) of tetrabutyl titanate to the above solution. React at 70-100°C for several hours, and remove the mixture of butanol and water by distillation. Cool the product to 60°C, and add 5.2 g (0.05 mol) of trimethyl borate and 50 g (0.375 mol) of 30 wt% sodium hydroxide aqueous solution to the above solution through a dropping funnel, and stir to obtain a uniform and transparent catalyst solution A.

[0035] Preparation of PBT polyester

[0036] 500 g of terephthalic acid (PTA), 450 g of 1,4-butanediol and catalyst A (based on the amount of polyester produced, the weight content of titanium atoms is 80×10 -6), add 2L polymerization reactor. Esterification reaction is carried out at 200-250℃ for 150 minutes. After the esterification is completed, the pressure is reduced to normal pressure, and the system pressure is reduced by vacuum to less than 150Pa. At the same time, the temperature is gradually increased to 230-260℃. After the reaction for 2 hours, the reaction is stopped, and the product is continuously extruded from the bottom of the polymerization reactor, cooled, and pelletized.

[0037] The test results of relevant esterification effluent, esterification products, slices, etc. are listed in Table 1.

[0038] [Example 2]

[0039] Add 262.5 g (1.25 mol) of citric acid monohydrate and 262.5 g of water to a three-necked flask equipped with an agitator, a condenser and a thermometer, and stir to dissolve. Use a dropping funnel to slowly add 170 g (0.5 mol) of tetrabutyl titanate to the above solution. React for several hours at 70-100°C, and remove the mixture of butanol and water by distillation. Cool the product to 60°C, and add 10.4 g (0.1 mol) of trimethyl borate and 50 g (0.375 mol) of 30 wt% sodium hydroxide aqueous solution to the above solution through a dropping funnel, and stir to obtain a uniform and transparent catalyst solution B.

[0040] Preparation of PBT polyester

[0041] 500 g of terephthalic acid (PTA), 450 g of 1,4-butanediol and catalyst B (based on the amount of polyester produced, the weight content of titanium atoms is 80×10 -6 ), add 2L polymerization reactor. Esterification reaction is carried out at 200-250℃ for 150 minutes. After the esterification is completed, the pressure is reduced to normal pressure, and the system pressure is reduced by vacuum to less than 150Pa. At the same time, the temperature is gradually increased to 230-260℃. After the reaction for 2 hours, the reaction is stopped, and the product is continuously extruded from the bottom of the polymerization reactor, cooled, and pelletized.

[0042] The test results of relevant esterification effluent, esterification products, slices, etc. are listed in Table 1.

[0043] [Example 3]

[0044] Add 262.5 g (1.25 mol) of citric acid monohydrate and 262.5 g of water to a three-necked flask equipped with a stirrer, a condenser and a thermometer, and stir to dissolve. Use a dropping funnel to slowly add 170 g (0.5 mol) of tetrabutyl titanate to the above solution. React for several hours at 70-100°C, and remove the mixture of butanol and water by distillation. Cool the product to 60°C, and add 2.6 g (0.025 mol) of trimethyl borate and 50 g (0.375 mol) of 30 wt% sodium hydroxide aqueous solution to the above solution through a dropping funnel, and stir to obtain a uniform and transparent catalyst solution C.

[0045] Preparation of PBT polyester

[0046] 500 g of terephthalic acid (PTA), 450 g of 1,4-butanediol and catalyst C (based on the amount of polyester produced, the weight content of titanium atoms is 80×10 -6 ), add 2L polymerization reactor. Esterification reaction is carried out at 200-250℃ for 150 minutes. After the esterification is completed, the pressure is reduced to normal pressure, and the system pressure is reduced by vacuum to less than 150Pa. At the same time, the temperature is gradually increased to 230-260℃. After the reaction for 2 hours, the reaction is stopped, and the product is continuously extruded from the bottom of the polymerization reactor, cooled, and pelletized.

[0047] The test results of relevant esterification effluent, esterification products, slices, etc. are listed in Table 1.

[0048] [Example 4]

[0049] Preparation of PBAT polyester

[0050] 266 g of terephthalic acid (PTA), 234 g of adipic acid, 450 g of 1,4-butanediol and catalyst A (based on the amount of polyester produced, the weight content of titanium atoms is 100×10 -6 ) was added to a 2L polymerization reactor. The esterification reaction was carried out at 160-220°C for 150 minutes. After the esterification was completed, the pressure was reduced to normal pressure and phosphoric acid (based on the amount of polyester produced, the weight content of phosphorus atoms was 60×10 -6 ), after stirring for several minutes, evacuate and reduce the pressure to a system pressure lower than 150Pa, and gradually raise the temperature to 240-255°C. After reacting for 2 hours, stop the reaction, and then continuously extrude, cool and pelletize the product from the bottom of the polymerization kettle.

[0051] The test results of relevant esterification effluent, esterification products, slices, etc. are listed in Table 1.

[0052] [Comparative Example 1]

[0053] Preparation of PBT polyester

[0054] 500 g of terephthalic acid (PTA), 450 g of 1,4-butanediol and tetrabutyl titanate (based on the amount of polyester produced, the weight content of titanium atoms is 80×10 -6 ), add 2L polymerization reactor. Esterification reaction is carried out at 200-250℃ for 150 minutes. After the esterification is completed, the pressure is reduced to normal pressure, and the system pressure is reduced by vacuum to less than 150Pa. At the same time, the temperature is gradually increased to 230-260℃. After the reaction for 2 hours, the reaction is stopped, and the product is continuously extruded from the bottom of the polymerization reactor, cooled, and pelletized.

[0055] The test results of relevant esterification effluent, esterification products, slices, etc. are listed in Table 1.

[0056] [Comparative Example 2]

[0057] Add 262.5 g (1.25 mol) of citric acid monohydrate and 262.5 g of water to a three-necked flask equipped with a stirrer, a condenser and a thermometer, and stir to dissolve. Use a dropping funnel to slowly add 170 g (0.5 mol) of tetrabutyl titanate to the above solution. React at 70-100° C. for several hours, and remove the mixture of butanol and water by distillation. Cool the product to 60° C., and add 50 g (0.375 mol) of 30 wt% sodium hydroxide aqueous solution to the above solution through a dropping funnel, and stir to obtain a uniform and transparent catalyst solution D.

[0058] Preparation of PBT polyester

[0059] 500 g of terephthalic acid (PTA), 450 g of 1,4-butanediol and catalyst D (based on the amount of polyester produced, the weight content of titanium atoms is 80×10 -6 ), add 2L polymerization reactor. Esterification reaction is carried out at 200-250℃ for 150 minutes. After the esterification is completed, the pressure is reduced to normal pressure, and the system pressure is reduced by vacuum to less than 150Pa. At the same time, the temperature is gradually increased to 230-260℃. After the reaction for 2 hours, the reaction is stopped, and the product is continuously extruded from the bottom of the polymerization reactor, cooled, and pelletized.

[0060] The test results of relevant esterification effluent, esterification products, slices, etc. are listed in Table 1.

[0061] [Example 5]

[0062] Catalyst hydrolysis test

[0063] Catalysts AD and tetrabutyl titanate were subjected to hydrolysis tests to explore the stability of the catalysts in water. The experimental method is briefly described as follows: First, the catalyst and water were mixed at a weight ratio of 9:1 to obtain a sample; then, the sample was heated at 200°C for 1 hour to perform a hydrolysis resistance test. The appearance of the sample before and after heating is summarized in Table 1.

[0064] Table 1

[0065]

[0066] It can be seen from Table 1 that:

[0067] (1) Compared with Comparative Example 1, the catalysts AD modified with hydroxy acid showed good hydrolysis resistance and could be stably dispersed in aqueous solution and maintained a clear state, while tetrabutyl titanate would quickly generate white turbidity after contacting water.

[0068] (2) Compared with Comparative Example 2 (Catalyst D), adding boric acid ester (Catalyst AC) to the catalyst can effectively reduce the problem of reduced esterification activity and polycondensation activity caused by hydrolysis resistance treatment of hydroxy acid, and improve the activity of the catalyst. For example, the acid value of the esterified product obtained in Example 1 is 168 mol / t (the lower the acid value, the higher the degree of esterification), which is close to the esterified product obtained by tetrabutyl titanate (Comparative Column 1) (164 mol / t), and lower than the acid value of the esterified product in Comparative Column 2 (180 mol / t). At the same time, the intrinsic viscosity of Example 1 is 1.05 dl / g (the higher the value, the higher the polycondensation activity), and the hue L / b (the higher the L value, the lower the b value, the better the slice quality) is 91.5 / 1.7, which are better than Comparative Example 2.

[0069] In summary, the catalyst composition of the present invention effectively improves the problem of reduced catalyst activity and deterioration of polyester quality caused by hydrolysis resistance modification of hydroxyl acid, can obtain high-quality polyester, and has good technical effects.

[0070] The present invention has been described in detail above in conjunction with specific embodiments, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements can be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A catalyst for the polymerization of polybutylene terephthalate and / or its copolyester, the catalyst comprising a titanium compound and a borate compound, wherein the molar ratio of the borate to the titanium compound is 0.01-0.5:1 in terms of boron element and titanium element, the titanium compound is a reaction product of a compound having the general formula Ti(OR)4 and a hydroxy acid, R is a straight chain or branched alkyl group selected from 1 to 10 carbon atoms, and the molar ratio of the compound having the general formula Ti(OR)4 to the hydroxy acid is 1:(1-4).

2. The catalyst for polymerization of polybutylene terephthalate and / or its copolyester according to claim 1, characterized in that The borate ester is at least one of trimethyl borate, triethyl borate, triisopropyl borate, tributyl borate, triethylene glycol borate, tripropylene glycol borate and tributyl glycol borate.

3. The catalyst for polymerization of polybutylene terephthalate and / or its copolyester according to claim 2, characterized in that: The catalyst further contains an alkali metal compound and / or an ammonium compound; the molar ratio of the alkali metal compound and / or the ammonium compound to the hydroxy acid is (0.05-0.5):

1.

4. The catalyst for polymerization of polybutylene terephthalate and / or its copolyester according to claim 3, characterized in that The catalyst further comprises a solvent, and the solvent is water and / or an alcohol solvent.

5. The method for preparing the catalyst for polymerization of polybutylene terephthalate and / or its copolyester according to claim 4, comprising: The catalyst is obtained by mixing (1) the Ti(OR)4 compound of the general formula, (2) the hydroxy acid compound, (3) the borate ester, (4) the alkali metal compound and / or ammonium compound and (5) the optional solvent; the molar ratio of the borate ester to the titanium compound is 0.01-0.5:1 in terms of boron element and titanium element; the molar ratio of the Ti(OR)4 compound of the general formula to the hydroxy acid is 1: (1-4); and the molar ratio of the alkali metal compound and / or ammonium compound to the hydroxy acid is (0.05~0.5):

1.

6. The preparation method according to claim 5, characterized in that: Also includes: (1) mixing the hydroxy acid compound and the optional solvent, and then adding the compound of the general formula Ti(OR)4 to obtain a mixed solution; (2) The mixed solution is subjected to a heating treatment, and then a boric acid ester and an alkali metal compound and / or an ammonium compound are added to obtain the catalyst solution.

7. The preparation method according to claim 6, characterized in that: In step (2), the temperature is raised to 50-200°C.

8. A method for preparing polybutylene terephthalate and / or its copolyester, characterized in that: (1) Using the catalyst of any one of claims 1 to 4 or using the preparation method of any one of claims 5 to 7 to obtain a catalyst; (2) synthesizing the catalyst in step (1) with polybutylene terephthalate and / or its copolyester to obtain a product.

9. Polybutylene terephthalate and / or its copolyester obtained by the method for preparing polybutylene terephthalate and / or its copolyester according to claim 8.

Citation Information

Patent Citations

  • Catalyst and process

    CN1720216A